2015
DOI: 10.1017/neu.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine levels in schizophrenia patients newly admitted to an acute psychiatric ward

Abstract: Hyperhomocysteinaemia, which occurred in our schizophrenia patients with poor social and relational functioning after many years of illness, could represent an effect of altered lifestyle due to psychosis, but not a specific marker for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
1
9
1
2
Order By: Relevance
“…With respect to Hcy, although it has been suggested that high levels are a risk factor for SCH [33, 5153], some studies, including our own research, find no differences between SCH patients and HC [35, 36].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…With respect to Hcy, although it has been suggested that high levels are a risk factor for SCH [33, 5153], some studies, including our own research, find no differences between SCH patients and HC [35, 36].…”
Section: Discussioncontrasting
confidence: 61%
“…For homocysteine (Hcy), an intermediate amino acid containing a sulfhydryl radical that can act as an oxidant, the results are controversial. While some studies found higher levels of this oxidative stress biomarker in several subgroups of SCH (31-33) compared with HC patients (31,34), others did not (35,36).…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, a recent large-sample study including 7872 subjects evaluated the age-related differences in Hcy levels in a general Chinese population and showed that the Hcy levels rst decreased, then increased, and signi cantly increased after 50 years of age 17 , similar to the results of our study. However, some previous studies did not observe a statistically signi cant association between Hcy levels and age 18 , whereas other studies reported that plasma Hcy levels increased signi cantly with age in the general population and patients with schizophrenia 19 ; 20 . The inconsistent results for this association are unclear.…”
Section: Discussionmentioning
confidence: 85%
“…Elevated plasma Hcy levels might also contribute to cognitive de cits that are common in patients with schizophrenia, even when the analyses are corrected for the relevant covariates 7 . However, several epidemiological studies have shown that elevated Hcy levels do not appear to be correlated with cognitive de cits in patients with schizophrenia 8 . Therefore, the association between Hcy levels and cognitive de cits in patients with schizophrenia continues to be debated.…”
Section: Introductionmentioning
confidence: 98%
“…39,40 Regland et al 41 were the first to associate increased blood Hcy concentrations with schizophrenia in 1995. The association was latter subject of a meta-analysis in 2006 by Muntjewerff et al 42 who collected data from 8 case-control studies and demonstrated a 70% increase in the risk of schizophrenia for every 5 mM increase in Hcy concentration and many other studies since then have corroborated this hypothesis, [43][44][45][46][47][48][49][50][51][52] although negative results are also present in the literature. 53 Genetic factors associated with Hcy metabolism are also associated with schizophrenia risk.…”
Section: Schizophreniamentioning
confidence: 97%